A Record Based Study of Electrocution Cases Brought at Mortuary Complex of Tertiary Care Center, Bhavnagar - Mandaliya , R N; Bavadiya , G L; Rana , N M; Parmar, A P (Journal of Indian Academy of Forensic Medicine, 2022)
Electrical appliances have become a part of our living. In modern era, persons of different professions are daily handling electricity and its related appliances’ while performing their day-to-day duties and activities. Although people are aware of the danger caused by non protective contact with electricity, but very few really understand that even a minute quantity of electrical energy is sufficient to cause electrocution-related fatalities. In this record study, an attempt being made to study the electrocution fatalities that were autopsied at tertiary care center, Bhavnagar during 1 year. During study period, 18 deaths (1.97%) due to electrocution were accidental in Nature. Majority of the people belonged to age group 21-30 which constituted 33.33 % (6 out of 18 cases) of the total cases studied. 15 (83%) cases were male and 3 (17%) cases were females. Hand was the most frequently involved electrical wound 12 deaths (66.67%). Out of 18 cases, 11 cases have occurred outside the home out of which, 10 cases occurred at work places. Out of 18 cases, 16 cases were dead on the spot. It signifies that work-related electrocution deaths require multidisciplinary attention and awareness.